Comparison of the effects of host-associated (autochthonous) and commercial probiotics on immune responses, growth parameters and intestinal microbiota of Caspian whitefish (Rutilus frisii kutum) fry - Hoseinifar, Seyed Hossein; Hoseini, Seyyed Morteza; Taheri Mirghaed, Ali; Ghelichpour, Melika; Shirzad-Aski, Hesamaddin; Van Doan, Hien; El-Haroun, Ehab; Safari, Roghieh; Khanzadeh, Majid (Frontiers in Marine Science, 2024)
Probiotics are helpful bacteria that safeguard host animals from harmful pathogens. In fish farming, the primary aim of using probiotics is to preserve or reestablish a balance between pathogenic microorganisms and the native bacteria that constitute the intestinal and skin microbial communities of fish. This study investigates the effects of host-associated probiotic (HAP) vs commercial probiotic (CP) on the growth performance, antioxidant defense and immunity of Caspian whitefish fry. Three hundred whitefish fry (1.15 ± 0.03 g) were randomly divided into five treatments in triplicate. Treatments included feeding with the control group (zero), P. acidilactici as a commercial probiotic (CP) at 6 × 108 CFU g -1, and HA Pediococcus pentosaceus at 106, 107 and 108 CFU g-1 for eight weeks. Dietary HAP and CP did not have significant effects on growth indices compared to the control group (P > 0.05). However, HAP at 107 and 108 CFU g-1 and CP significantly increased protein in whitefish carcasses compared to the control group (P < 0.05). Different levels of HAP and CP had a significant effect on whole-body extract (WBE) lysozyme (LZM) activity (P < 0.05). HAP treatment significantly increased WBE ACH50 and bactericidal activity compared to the control and CP group (P < 0.05). Also, in the case of mucosal immune response, different levels of HAP could significantly increase LZM, total immunoglobulin (Ig), agglutination titer, protease and alkaline phosphatase activity compared to the control group (P < 0.05). Whitefish fed HAP showed a significant increase in the activity of WBE antioxidant parameters (SOD, CAT and GPx) compared to the control group (P < 0.05). Also, feeding with HAP could significantly increase autochthonous LAB levels compared control group (P < 0.05); while the total count of intestinal heterotrophic bacteria was not affected (P > 0.05). Overall, the present study showed HA Pediococcus pentosaceus can be considered as beneficial feed additive for whitefish.